ChemInform Abstract: Silver‐Mediated Direct Phosphorylation of Benzothiazoles and Thiazoles with Diarylphosphine Oxides. Issue 28 (July 2015) - Zhang, Hui‐Jun; Lin, Weidong; Wu, Zhengjian; Ruan, Wenqing; Wen, Ting‐Bin
Abstract The convenient, efficient protocol for the phosphorylation of the title compounds furnishes 2‐diarylphosphoryl‐substituted products under mild conditions.